MAYBE Initial complexity problem: 1: T: (1, 1) f0(a, b, c) -> f1(a, b, c) (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a, b, c) with all transitions in problem 1, the following new transitions are obtained: f0(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] We thus obtain the following problem: 2: T: (1, 2) f0(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] with all transitions in problem 2, the following new transitions are obtained: f0(a, b, c) -> f1(a + 2*c - 1, b, c - 2) [ a >= 1 /\ a + c >= 1 ] f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] We thus obtain the following problem: 3: T: (1, 3) f0(a, b, c) -> f1(a + 2*c - 1, b, c - 2) [ a >= 1 /\ a + c >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 2*c - 1, b, c - 2) [ a >= 1 /\ a + c >= 1 ] with all transitions in problem 3, the following new transitions are obtained: f0(a, b, c) -> f1(a + 3*c - 3, b, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] We thus obtain the following problem: 4: T: (1, 4) f0(a, b, c) -> f1(a + 3*c - 3, b, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 3*c - 3, b, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] with all transitions in problem 4, the following new transitions are obtained: f0(a, b, c) -> f1(a + 4*c - 6, b, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] We thus obtain the following problem: 5: T: (1, 5) f0(a, b, c) -> f1(a + 4*c - 6, b, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 4*c - 6, b, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] with all transitions in problem 5, the following new transitions are obtained: f0(a, b, c) -> f1(a + 5*c - 10, b, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] We thus obtain the following problem: 6: T: (1, 6) f0(a, b, c) -> f1(a + 5*c - 10, b, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 5*c - 10, b, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] with all transitions in problem 6, the following new transitions are obtained: f0(a, b, c) -> f1(a + 6*c - 15, b, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] We thus obtain the following problem: 7: T: (1, 7) f0(a, b, c) -> f1(a + 6*c - 15, b, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 6*c - 15, b, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] with all transitions in problem 7, the following new transitions are obtained: f0(a, b, c) -> f1(a + 7*c - 21, b, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] We thus obtain the following problem: 8: T: (1, 8) f0(a, b, c) -> f1(a + 7*c - 21, b, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 8) f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 7*c - 21, b, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] with all transitions in problem 8, the following new transitions are obtained: f0(a, b, c) -> f1(a + 8*c - 28, b, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] f0(a, b, c) -> f1(a + 7*c + b - 21, b - 1, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] We thus obtain the following problem: 9: T: (1, 9) f0(a, b, c) -> f1(a + 8*c - 28, b, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (1, 9) f0(a, b, c) -> f1(a + 7*c + b - 21, b - 1, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (1, 8) f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 8*c - 28, b, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] with all transitions in problem 9, the following new transitions are obtained: f0(a, b, c) -> f1(a + 9*c - 36, b, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] f0(a, b, c) -> f1(a + 8*c + b - 28, b - 1, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] We thus obtain the following problem: 10: T: (1, 10) f0(a, b, c) -> f1(a + 9*c - 36, b, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] (1, 10) f0(a, b, c) -> f1(a + 8*c + b - 28, b - 1, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] (1, 9) f0(a, b, c) -> f1(a + 7*c + b - 21, b - 1, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (1, 8) f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 9*c - 36, b, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] with all transitions in problem 10, the following new transitions are obtained: f0(a, b, c) -> f1(a + 10*c - 45, b, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] f0(a, b, c) -> f1(a + 9*c + b - 36, b - 1, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] We thus obtain the following problem: 11: T: (1, 11) f0(a, b, c) -> f1(a + 10*c - 45, b, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] (1, 11) f0(a, b, c) -> f1(a + 9*c + b - 36, b - 1, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] (1, 10) f0(a, b, c) -> f1(a + 8*c + b - 28, b - 1, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] (1, 9) f0(a, b, c) -> f1(a + 7*c + b - 21, b - 1, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (1, 8) f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 10*c - 45, b, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] with all transitions in problem 11, the following new transitions are obtained: f0(a, b, c) -> f1(a + 11*c - 55, b, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] f0(a, b, c) -> f1(a + 10*c + b - 45, b - 1, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] We thus obtain the following problem: 12: T: (1, 12) f0(a, b, c) -> f1(a + 11*c - 55, b, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] (1, 12) f0(a, b, c) -> f1(a + 10*c + b - 45, b - 1, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] (1, 11) f0(a, b, c) -> f1(a + 9*c + b - 36, b - 1, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] (1, 10) f0(a, b, c) -> f1(a + 8*c + b - 28, b - 1, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] (1, 9) f0(a, b, c) -> f1(a + 7*c + b - 21, b - 1, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (1, 8) f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 11*c - 55, b, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] with all transitions in problem 12, the following new transitions are obtained: f0(a, b, c) -> f1(a + 12*c - 66, b, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] f0(a, b, c) -> f1(a + 11*c + b - 55, b - 1, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] We thus obtain the following problem: 13: T: (1, 13) f0(a, b, c) -> f1(a + 12*c - 66, b, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] (1, 13) f0(a, b, c) -> f1(a + 11*c + b - 55, b - 1, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] (1, 12) f0(a, b, c) -> f1(a + 10*c + b - 45, b - 1, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] (1, 11) f0(a, b, c) -> f1(a + 9*c + b - 36, b - 1, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] (1, 10) f0(a, b, c) -> f1(a + 8*c + b - 28, b - 1, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] (1, 9) f0(a, b, c) -> f1(a + 7*c + b - 21, b - 1, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (1, 8) f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 12*c - 66, b, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] with all transitions in problem 13, the following new transitions are obtained: f0(a, b, c) -> f1(a + 13*c - 78, b, c - 13) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] f0(a, b, c) -> f1(a + 12*c + b - 66, b - 1, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] We thus obtain the following problem: 14: T: (1, 14) f0(a, b, c) -> f1(a + 13*c - 78, b, c - 13) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] (1, 14) f0(a, b, c) -> f1(a + 12*c + b - 66, b - 1, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] (1, 13) f0(a, b, c) -> f1(a + 11*c + b - 55, b - 1, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] (1, 12) f0(a, b, c) -> f1(a + 10*c + b - 45, b - 1, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] (1, 11) f0(a, b, c) -> f1(a + 9*c + b - 36, b - 1, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] (1, 10) f0(a, b, c) -> f1(a + 8*c + b - 28, b - 1, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] (1, 9) f0(a, b, c) -> f1(a + 7*c + b - 21, b - 1, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (1, 8) f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 13*c - 78, b, c - 13) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] with all transitions in problem 14, the following new transitions are obtained: f0(a, b, c) -> f1(a + 14*c - 91, b, c - 14) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 ] f0(a, b, c) -> f1(a + 13*c + b - 78, b - 1, c - 13) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 ] We thus obtain the following problem: 15: T: (1, 15) f0(a, b, c) -> f1(a + 14*c - 91, b, c - 14) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 ] (1, 15) f0(a, b, c) -> f1(a + 13*c + b - 78, b - 1, c - 13) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 ] (1, 14) f0(a, b, c) -> f1(a + 12*c + b - 66, b - 1, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] (1, 13) f0(a, b, c) -> f1(a + 11*c + b - 55, b - 1, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] (1, 12) f0(a, b, c) -> f1(a + 10*c + b - 45, b - 1, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] (1, 11) f0(a, b, c) -> f1(a + 9*c + b - 36, b - 1, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] (1, 10) f0(a, b, c) -> f1(a + 8*c + b - 28, b - 1, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] (1, 9) f0(a, b, c) -> f1(a + 7*c + b - 21, b - 1, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (1, 8) f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a + 14*c - 91, b, c - 14) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 ] with all transitions in problem 15, the following new transitions are obtained: f0(a, b, c) -> f1(a + 15*c - 105, b, c - 15) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 /\ a + 14*c - 91 >= 1 ] f0(a, b, c) -> f1(a + 14*c + b - 91, b - 1, c - 14) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 /\ a + 14*c - 91 >= 1 ] We thus obtain the following problem: 16: T: (1, 16) f0(a, b, c) -> f1(a + 15*c - 105, b, c - 15) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 /\ a + 14*c - 91 >= 1 ] (1, 16) f0(a, b, c) -> f1(a + 14*c + b - 91, b - 1, c - 14) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 /\ a + 14*c - 91 >= 1 ] (1, 15) f0(a, b, c) -> f1(a + 13*c + b - 78, b - 1, c - 13) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 ] (1, 14) f0(a, b, c) -> f1(a + 12*c + b - 66, b - 1, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] (1, 13) f0(a, b, c) -> f1(a + 11*c + b - 55, b - 1, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] (1, 12) f0(a, b, c) -> f1(a + 10*c + b - 45, b - 1, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] (1, 11) f0(a, b, c) -> f1(a + 9*c + b - 36, b - 1, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] (1, 10) f0(a, b, c) -> f1(a + 8*c + b - 28, b - 1, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] (1, 9) f0(a, b, c) -> f1(a + 7*c + b - 21, b - 1, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (1, 8) f0(a, b, c) -> f1(a + 6*c + b - 15, b - 1, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (1, 7) f0(a, b, c) -> f1(a + 5*c + b - 10, b - 1, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (1, 6) f0(a, b, c) -> f1(a + 4*c + b - 6, b - 1, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (1, 5) f0(a, b, c) -> f1(a + 3*c + b - 3, b - 1, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (1, 4) f0(a, b, c) -> f1(a + 2*c + b - 1, b - 1, c - 2) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (1, 3) f0(a, b, c) -> f1(a + c + b, b - 1, c - 1) [ a >= 1 /\ a + c >= 1 ] (1, 2) f0(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + b, b - 1, c) [ a >= 1 ] (?, 1) f1(a, b, c) -> f1(a + c, b, c - 1) [ a >= 1 ] start location: f0 leaf cost: 0 Complexity upper bound ? Time: 5.866 sec (SMT: 5.570 sec)